2005
DOI: 10.1021/np0580053
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpene Lactones from the Seeds of Nephelium lappaceum

Abstract: Dichloromethane extracts of the seeds of Nephelium lappaceum afforded two new diastereomeric monoterpene lactones, 1 and 2, and the known butenolide siphonodin (3), as well as kaempferol 3-O-beta-D-glucopyranoside-7-O-alpha-L-rhamnopyranoside. Compounds 1 and 2 represent a new monoterpene skeleton, and their structures were elucidated by extensive 1D and 2D NMR spectral data interpretation. Antimicrobial testing was carried out on 1 and 2 against a panel of bacteria and fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…), and mamoncillo (Melicoccus bijugatus Jacq.). As a multifunctional medicinal plant, the roots show anti-fever effects [2], the bark is an astringent [2], the leaves are used as poultices [2], the pericarp can reduce the mortality of infections caused by herpes simplex virus type 1 [3], and the pulp can be used for the treatment of severe dysentery and type 2 diabetes mellitus [4], although it has been reported that it could cause anaphylaxis [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and mamoncillo (Melicoccus bijugatus Jacq.). As a multifunctional medicinal plant, the roots show anti-fever effects [2], the bark is an astringent [2], the leaves are used as poultices [2], the pericarp can reduce the mortality of infections caused by herpes simplex virus type 1 [3], and the pulp can be used for the treatment of severe dysentery and type 2 diabetes mellitus [4], although it has been reported that it could cause anaphylaxis [5].…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies have been performed on bioactivity of the seeds [2]. For example, the insecticidal activity of the rambutan seeds was associated with type II cyanolipid components [6].…”
Section: Introductionmentioning
confidence: 99%
“…Native to Southeast Asia, rambutan is cultivated for its fruit and sold commercially [1,2]. It is consumed fresh, canned, or processed, and appreciated for its refreshing flavor and exotic appearance [3].…”
mentioning
confidence: 99%
“…It is consumed fresh, canned, or processed, and appreciated for its refreshing flavor and exotic appearance [3]. The seeds are bitter and narcotic, with the roots used for treating fevers, the leaves as poultices, and the bark as an astringent [2]. The rind of rambutan, which is normally discarded, was found to contain extremely high antioxidant and antibacterial activities, and several potential antioxidant activities, including reducing power, E-carotene bleaching, linoleic peroxidation, and free radical scavenging activity, were also exhibited [4,5].…”
mentioning
confidence: 99%
“…aurantiacus that differed primarily by the presence of sterol acetates. Cholesterol acetate was isolated previously from green algae [14] and mutant yeast cells [15]; sitosterol acetate (24R-ethylcholest-5-en-3E-ol), from higher plants [16][17][18]. The remaining components found in the sterolacetate fractions should probably be considered to be new natural compounds.…”
mentioning
confidence: 99%